2005
DOI: 10.2134/agronj2005.0129
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐to‐Plant Variability in Corn Production

Abstract: resulting in an estimated 1066 kg ha Ϫ1 (17 bu ac Ϫ1 ) yield loss over 354 commercial fields. Lauer and Rankin Corn (Zea mays L.) grain yields are known to vary from plant to (2004) and Liu et al. (2004) had differing results, noting plant, but the extent of this variability across a range of environments has not been evaluated. This study was initiated to evaluate by-plant that PSV did not significantly alter grain yields in Wiscorn grain yield variability over a range of production environments consin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 22 publications
(22 reference statements)
3
47
0
4
Order By: Relevance
“…Nielsen (2001) reported that plants that are next to a gap produced larger ears. Martin et al (2005) found an average difference equivalent to 2765 kg ha -1 plant to plant difference in corn yield. They further noted that production methods that homogenize plant stands and emergence, should decrease plantto-plant variation and will likely lead to increased yields.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Nielsen (2001) reported that plants that are next to a gap produced larger ears. Martin et al (2005) found an average difference equivalent to 2765 kg ha -1 plant to plant difference in corn yield. They further noted that production methods that homogenize plant stands and emergence, should decrease plantto-plant variation and will likely lead to increased yields.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Apart from that, the general soil quality degradation under zero tillage with residue removal caused stressful conditions. Stressful conditions increase plant-to-plant competition for resources and this competition results in greater plant variability (Martin et al 2005). The zero tillage practice with residue removal caused a non-uniform distribution of crop performance within the field, indicating the inefficient use of available resources with consequent yield losses, since in some parts of the field a higher yield was achieved than in others within the specific conditions of climate and germplasm.…”
Section: Comparing Patterns In Soil Attributes and Crop Performancementioning
confidence: 99%
“…Data collected by Martin et al (2005) from locations in Argentina, Mexico, Iowa, Nebraska, Ohio, Virginia, and Oklahoma showed that regardless of location, plant-to-plant variability in corn grain yield averaged more than 2765 kg ha −1 over sites and years. They further noted that plant-to-plant variability in corn grain yield can be expected in virtually all production environments.…”
Section: Introductionmentioning
confidence: 99%